Iot Based Production Monitoring In Industry Using Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2018)
The objective of the project is to monitoring the production lines in industry  using  wireless sensor networks. This project presents the benefits of an automated data collection and display system for production lines. It involves wireless sensor networks for monitoring the productions in industry.  Condition monitoring reduces human inspection requirements through automated monitoring, reduces  maintanence through detecting faults before they escalate and improves safety and reliability. This work can monitor productions using temperature, voltage and current sensors with support of microcontroller. Relay is acts like a switch to monitor the production lines.   In this project Global System for Mobile communication technique is used to transferring the  collected data. The collection of data, it is transferred into computerize spreadsheet in the remote office by authorized personnel for reporting purpose. The system will generate an automated report which stays in place and the management only needs to act base on the results. This project is cost effective automatic data collection is the alternative to manual data collection. It significantly improves the accuracy of the valuable reports for the management. It also reduces the time for identifying the fault using this technique.